CLIMATE CHANGE: CAUSES AND CONSEQUENCES - Hernández, Yoleida
The interest of the research focused on analyzing climate change its known causes and its consequences, using for this a process of consultation in documents and texts, with whose interpretation it was possible to obtain and compile the required information regarding the determining causes of climate change and its consequences for the habitat. Finding environmental effects caused by the increase in the concentration in the atmosphere of the main greenhouse effect gases (GHG) such as carbon dioxide (CO2), methane (CH4), nitrous oxide (N2O) and chlorofluorocarbons (CFC's ), results of human activities that have intensified the use of fossil fuels in industrialization, energy, transportation, mining, deforestation, among others, concluding that they are the causes that have caused serious changes in the climate at a global level, translated into floods , drought, hurricanes and all kinds of natural disasters.